Gestão da informação no terceiro setor: o caso do projeto Garotada Solidária desenvolvido pela organização não-governamental Amazona - Araújo, Claudialyne da Silva (2013)
In the contemporary society, information and knowledge became strategic resources which encompass transmission, valuation, storage, distribution and dissemination of information as central elements of economic activities of the organizations. In this scenario emerges the constant concern with the social reality where people make part of. Such concerns are related to social exclusion and inclusion where it is observed the strengthening of the organizations with reference to the third sector, more precisely the NGOs (nongovernmental organizations) that act providing an important contribution to the social development. In this way, information management acts as strategic element for the fulfillment of projects that have information as central and essential element. Therefore, the use of information management in this process has become indispensable. This research aimed at analyzing the actions that compose the information management process adopted in the PGS implementation developed by the Amazona NGO that works with preventive information through the awareness of young persons about the STD/AIDS contagion in five communities that are in risk situation, located around the city of João Pessoa PB. The research was conducted from the theoretical fundamentals of Information Science and for its accomplishment the information management model proposed by McGee & Prusak (1994) was used. It is a qualitative research whose method was the case study due to the need of developing a deeper and comprehensive study with the objective to obtain wide and detailed knowledge of the studied object. By means of data collection and analysis, it was perceived that the process of information management is carried out in a nonplanned and structured way. This reduces the potential it could have in the fulfillment of the objectives to which the project is proposed. In some communities, the results were unsatisfactory due to this weakness. There was the interference of different problems that could not be solved satisfactorily and this affected the expected success.